The Relationship of Working Period and Low Back Pain Complaints in Weaning Workers at Ulos Sianipar Gallery - Yurisna, Nabila; Harahap, Reni Agustina (Universitas Ibn Khaldun Bogor, 2024)
Low back pain in indonesian means lower back pain is a health problem that often occurs in society, especially in weaving workers who carry out repetitive movements. Working for a long period of time is one of the risk factors for low back pain. The aim of this research is to determine the relationship between length of service and complaints of low back pain among weaving workers at the ulos sianipar gallery. This research uses quantitative methods with a cross sectional study. Samples were taken using a total sampling technique. The number of samples used in this research was 45 weaving workers at the ulos sianipar gallery. Data analysis was carried out univariate and bivariate using the chi square test. The results of this study show that there is a relationship between length of service and complaints of low back pain in weaving workers with a p Value of 0,002. It is also hoped that business owners can provide rest time for weaving workers and also provide a special rest room for weaving workers which can be used during rest time to reduce lower back pain.